Developing the hybrid model (waqf & zakat) for improving the zakat recipients healthcare In Selangor - Shaiq Ahmad, Ghafoorzai; Bilal Khan, Mohammad; Patel, Ibadurrehman; Mohammed Shehbaz, Damkar; Sharofiddin, Ashurov (2020)
The paper aims to develop a model that will enhance the healthcare of zakat recipients through the cooperation of waqf and zakat institutions. As per reports, there are enough waqf and zakat assets in Selangor which are unutilized. Thus, to utilize the barren and unutilized assets of waqf and Zakat, a better management system is required to overcome these issues. This study uses the qualitative method to achieve its objectives through content analysis which involves previously established data including journals, reports, and online data related to the topic which is then analyzed thoroughly to collect the relevant data. Moreover, it is found in the study that the Zakat fund can be used for investment purposes and it holds significance in terms of improving the healthcare of zakat recipients and leading the society towards achieving social well-being. The results of this study may contribute to enhancing the understanding of policymakers. In addition, it will not only enhance zakat collection and distribution but also contribute to the efficient management of Waqf and zakat funds